How Much Multinational Corporations Pay in Taxes and Where: Evidence from their Country-by-Country Reports - Tommaso Faccio; Sarah Godar; Patr Jansky; Oliver Seabarron (Charles University in Prague, Institute of Economic Studies (IES), 2021)
By exploiting country-by-country reports (CBCRs) prepared according to the OECD BEPS Action 13's minimum standards and voluntarily published by multinational corporations (MNCs), we show that the CBCR data can be used to identify how much MNCs pay in taxes and where, as well as how important tax havens and profit shifting are. The largest, hand-collected sample of these CBCRs combines global information from ten MNCs, which are special not only in terms of tax transparency, by being the only MNCs to publish their CBCR, but also in terms of industry composition, with a half of them in the extractive industries, and - perhaps, therefore - the observed tax characteristics. Specifically, we observe that the worldwide effective tax rates of our sample MNCs are higher on average than our comparison estimates based on the aggregate data for large MNCs published in 2020. We also find that the sample MNCs report slightly more profits in tax havens on average than many large MNCs, although most of the sample MNCs are far below that average. We further find some indication of profit shifting as the sample MNCs' profits in tax havens are much higher than their economic activity suggests and we estimate a non-linear relationship between profits and effective tax rates, which is negative up to effective tax rates of around 30%. We highlight the differences across countries and MNCs by presenting country-level results, both for the whole sample and for specific MNCs, but CBCR data for even more individual MNCs would be needed to test for any systematic, MNC-specific determinants behind these differences.
Keywords: F23; H25; H26; 330; multinational corporation; country-by-country reporting; effective tax rate; profit shifting; tax haven